"Dioxins are the easiest topic to mention": Resident activists' construction of knowledge about low-level exposure to toxic chemicals. (April 2016) - Andersen, Nina Blom
This article discusses how residents in a local area contributed to the construction of knowledge in regard to scientific assessments in relation to a fire in a storage dump of burnable waste. Building on analytical concepts primarily from Social Worlds theory as well as some concepts from Actor–Network Theory, the analysis shows how dissent and a number of scientific controversies were initiated by some residents living nearby the waste dump who proved to be excellent network builders and who built a number of alliances with media and independent scientists, thus questioning the authorities' and their experts' legitimacy. Furthermore, the situated analysis identifies how a few persons—not very organized—were able to create a debate about scientific matters using their combined resources and strong alliance-building abilities, thus proving that in some cases there is no need for a higher level of organization.